Wanita dan syariah - Mohd, Azizah (2013)
Women are unique in their own way. They are one of the perfect creation of Allah s.w.t created to complete the life of a man as men's life partner leading a social life. This is specially mentioned in the Quran, Surah al-Hujurat verse 1. Nevertheless, in measuring the best person among man and woman, the Quran emphasizes the element of piety or taqwa. So the best of them is the most piety among them. This paper seeks to examine the rules of Islamic law (Shari'ah) that governs the rights and duties of a woman before and after her marriage. It is believed that the findings of this paper will benefit the whole who seek knowledge on women and the Shar'iah.